Genetic analysis of productive and reproductive traits in multiple-breed dairy cattle populations - Ribeiro, Virginia Mara Pereira; Merlo, Fernanda Albuquerque; Gouveia, Gabriela Canabrava; Winkelstroter, Larissa Kretli; Alves Abreu, Luiza Rodrigues; da Silva, Marcos Vinicius Gualberto Barbosa; Panetto, João Cláudio do Carmo; Paiva, Leandro de Carvalho; Cembranelli, Marcello de Aguiar Rodrigues; Toral, Fabio Luiz Buranelo (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to determine whether the random regression model using linear splines (RRMLS) is suitable to estimate the genetic parameters for productive and reproductive traits of a multiple-breed dairy cattle population, as well as to investigate the effect of the genetic group of the progeny on the genetic merit of the sire. The multiple-trait model (MTM) and the RRMLS with one knot fitted for every genetic group were used to obtain the genetic parameters. Records of 1/2 Holstein + 1/2 Gyr (1/2HG), 5/8 Holstein + 3/8 Gyr (5/8HG), and 3/4 Holstein + 1/4 Gyr (3/4HG) crossbreed dams were considered. The RRMLS showed better fitting. The additive and residual variances estimated by the MTM and the RRMLS were similar. Heritability varied from 0.20 to 0.33 for age at first calving, from 0.09 to 0.22 for first lactation length, and from 0.15 to 0.35 for first lactation 305-day milk yield, according to the genetic composition of the dams. The RRMLS is suitable to estimate the genetic parameters for productive and reproductive traits of multiple-breed dairy cattle populations. The genetic merit of the sires is affected by the genetic group of the progeny by which they are evaluated.